(untitled) (Research, Society and Development, 2022)
The objective was to carry out a technological and bibliographic survey regarding the application of polymeric materials in the development of products based on the water-soluble plant extract in powder of the babassu coconut (Orbignya sp). Prospecting was carried out in the databases of INPI, EPO, USPTO and WIPO to survey patents and in the databases of SciELO, Scopus and Web of Science journals to search for articles. 46 patents were found, but only two of them were cataloged in subclass A23L of the International Patent Classification (food products or non-alcoholic beverages, their preparation or treatment), but none were related to the production of plant-based milk, let alone the application of a polymer in the process. With the articles researched, it was observed that even though no patent records were found, there are studies that have already been addressing the preparation of powdered plant extracts based on the use of babassu almonds, mainly bringing to light the use of polymers in their methodologies, such as maltodextrin as a means of optimizing spray drying of milk, or acacia as an encapsulating agent. The application of these polymers is promising if correctly combined in the formulation of the babassu coconut powder water-soluble plant extract.